The Development of an Appropriate Psychology: The Work of the Organisation of Appropriate Social Services in South Africa - VOGELMAN, LLOYD (PINS-Psychology in Society, 2025)
Before addressing the question of what is an appropriate psychology in South Africa and OASSSA’s contribution to it, let me give you a brief history and description of OASSSA. OASSSA was established in 1983 and represents progressive psychologists, psychiatrists, social workers and other individuals interested in relevant social and health services. OASSSA was formed out of an ad hoc committee of progressive mental health professionals and students who felt both angry and disenchanted at the Institute of Family and Marital Therapy for holding a Family Conference at Sun City. The idea of discussing family dynamics and therapy within a homeland setting which is responsible for the break-up of thousands of families was seen as insensitive and anti-social. Since then OASSSA has grown enormously and we have members scattered throughout the country, and have major branches, one in the Transvaal and one in the Cape. Work within OASSSA takes a variety of forms, –emergency services training, research, education, media and information, therapeutic treatment. I will focus more specifically on these activities later in my paper.